A Negative (1,3)-β-D-Glucan Result Alone Is Not Sufficient to Rule Out a Diagnosis of Pneumocystis Pneumonia in Patients With Hematological Malignancies - Damiani, Céline; Demey, Baptiste; Pauc, Cécile; Le Govic, Yohann; Totet, Anne (Frontiers in Microbiology, 2021)
Background: Serum (1,3)-β-D-glucan (BG) testing is increasingly being used in the diagnostic armamentarium for invasive fungal diseases. Given its high sensitivity, some studies suggest that a negative BG result contributes to rule out a diagnosis of Pneumocystis pneumonia (PCP). However, recent reports described a suboptimal sensitivity in HIV-negative immunocompromised patients. In this study, we evaluated the performance of BG assay for PCP diagnosis in HIV-negative patients with diverse PCP risk factors. We also assessed the correlation between P. jirovecii load in pulmonary samples and serum BG levels. Methods: We retrospectively included HIV-negative patients with microscopically proven PCP and for whom a BG result was available. We also enrolled patients colonized by Pneumocystis as control group. Colonized patients were matched with PCP patients based on their underlying condition that exposed to PCP. Pulmonary fungal loads were determined by an in-house real-time PCR and BG levels were measured by using the Fungitell® kit (Associates of Cape Cod, Inc.). Results: Thirty-nine patients were included in each of the two groups. Thirty-four of 39 PCP patients and one of 39 colonized patient had a positive BG test, resulting in a sensitivity of 0.87 (95% CI: 0.73-0.94), a specificity of 0.97 (95% CI: 0.87-0.99), a positive predictive value of 0.97 (95% CI: 0.85-0.99) and a negative predictive value of 0.88 (95% CI: 0.75-0.95) for BG assay. Nonetheless, median BG level differed according to the underlying condition. Among the PCP group, the lowest median level of 211 pg/mL was observed in patients with hematological malignancy (HM) and differed significantly from that observed either in solid organ transplants (3473 pg/mL) or in patients with autoimmune or inflammatory disorder (3480 pg/mL). Indeed, the sensitivity of BG assay was estimated at 0.64 (95% CI: 0.35-0.85) in HM-patients and was lower than the one observed in the whole PCP group. Furthermore, BG level and fungal burden correlated poorly among all PCP patients. Conclusion: BG is not a reliable biomarker for ruling out PCP in HIV-negative patients with HM. Interpretation of a negative BG result should take into account, but not be limited to, the underlying condition predisposing to PCP.